1972
DOI: 10.1021/ic50107a030
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin delocalization in antiferromagnetic dimeric copper(II) benzoates

Abstract: The copper(II) salts of benzoic acid, o-, m-, and ^-methylbenzoic acid, and 2,6-dimethyl-and 3,5-dimethylbenzoic acid exist as dimers with reduced magnetic moments in acetone solution at room temperature. The solution nmr spectra of these compounds, as well as of [Cu(formate)z•urea]2 and [CuiacetateVureaL, exhibit quite large contact shifts of the proton resonances, consistent with a superexchange mechanism for the spin exchange. The pattern of signs of the contact shifts suggests that spin delocalization from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…[9][10][11][12][13][14] ), as well as Cu 2 + -substituted aminopeptidase, [9] appear to give relatively sharp NMR signals. As in the case of Ty, these Cu 2 compounds carry two closely spaced magnetically coupled copper atoms.…”
Section: Introductionmentioning
confidence: 94%
“…[9][10][11][12][13][14] ), as well as Cu 2 + -substituted aminopeptidase, [9] appear to give relatively sharp NMR signals. As in the case of Ty, these Cu 2 compounds carry two closely spaced magnetically coupled copper atoms.…”
Section: Introductionmentioning
confidence: 94%
“…Although NMR spectroscopy has been successfully used to investigate the structural and bonding properties of metal complexes, NMR studies of paramagnetic copper(II) complexes are fewer due to their inherent slow electronic relaxation time, leading to broadened signals . On the other hand, antiferromagnetically coupled copper(II) complexes are expected to give relatively narrow NMR signals. However, there are still few reports that demonstrate the usefulness of NMR spectra of binuclear Cu(II) complexes in solution. …”
Section: Introductionmentioning
confidence: 99%
“…13,141 H NMR spectra have been reported for antiferromagnetically and ferromagnetically coupled systems and both provide relatively sharp, hyperfine shifted 1 H NMR signals. 13,[15][16][17][18][19][20][21][22][23] However, the majority of the studies reported to date have relied on laborious synthetic methods such as substitution or deuteration to assign only a portion of the observed isotropically shifted signals. Therefore, 1 H NMR spectroscopy has been of little utility as a structural or magnetic probe of dicopper(II) centers.…”
Section: Introductionmentioning
confidence: 99%